Clostridium butyricum improves the digestive enzyme activity, antioxidant and immunity related genes expression and intestinal microbiota of Litopenaeus vannamei fed a replacing fishmeal with cottonseed protein concentrate (CPC) diet - Lixian Li; Hongyu Liu; Weikang Li; Qi Wang; Zhixuan Lin; Beiping Tan; Xiaohui Dong; Ruitao Xie (Aquaculture Reports, 2023)
The combined application performance of CPC and CB in shrimp diet is rarely explored. This experiment was conducted to investigate the effects of Clostridium butyricum (CB) on the body composition, digestive enzyme activity, antioxidant and immunity related genes expression and intestinal microbiota of Litopenaeus vannamei fed a replacing fishmeal with cottonseed protein concentrate (CPC) diet. Six diets were formulated with PC group (containing 30% fishmeal), NC and NCB1–4 groups (diet replacing 30% fishmeal protein with CPC), in which NCB1–4 groups were supplemented with 0.03% (3 ×108 CFU/kg), 0.12% (1.2 ×109 CFU/kg), 0.48% (4.8 ×109 CFU/kg) and 1.92% (1.92 ×1010 CFU/kg) CB, respectively. Healthy shrimp were randomly divided into 6 groups for an 8-week feeding trial. The CB antibacterial tests in vitro showed that the CB could inhibit the growth of Vibrio harveyi and V. parahaemolyticus, and has good thermal stability and tolerance to protease, catalase and ultraviolet irradiation. In feeding trial, the crude protein of NCB4 was significantly increased and the crude lipid in NCB3 and NCB4 group were significantly decreased (P < 0.05). Amylase, trypsin and lipase in hepatopancreas of NCB4 group increased significantly (P < 0.05). Muscle thickness of intestine in PC and NCB4 groups was significantly decrease (P < 0.05). Under CB supplementation, the relative expression of antioxidant-related genes (superoxide dismutase, catalase and glutathione peroxidase) in hepatopancreas and intestine increased significantly (P < 0.05); the relative expression of immune-related genes (toll protein, myeloid differentiation factor 88, transcription factor Dorsal, innate immune deficiency gene, transcription factor Relish, prophenoloxidase and lysozyme) in hepatopancreas and intestine increased significantly (P < 0.05). The intestinal microbiota analysis showed that CB reduced the relative abundance of Proteobacteria, Tenericutes and Bacteroidetes, while increased the relative abundance of Firmicutes. Overall, shrimp supplement exceeds 3 × 108 CFU/kg had a clear benefit. Based on the relative expression of Relish in intestine, the recommended supplementation of CB is 1.37 × 1010 CFU/kg.